IDENTIFICATION OF POTENTIAL HAZARDS ON PRODUCTION MACHINES WITH HAZOPS AND FISHBONE DIAGRAM IN PT. SILINDER KONVERTER INTERNASIONAL - Bastuti, Sofian; TH, Estiningsih (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2021)
PT. Silinder Konverter Internasional is a company in the field of Rotogravure Cylinders. The company is a chemical sector industry and has only been running for about 2 years, for that the company needs to pay attention to the issues of Occupational Safety and Health because this greatly affects the company's productivity. The purpose of this study was to identify the factors causing occupational safety and health hazards to avoid work accidents at PT. Silinder Konverter Internasional. From the results of the research using the Hazards Operability Study (HAZOPS) method, there was 38 potential (40%) chemical potential hazards, 28 potential (29.47%) overwritten materials, 14 potential scratches (14.73%), 12 potential pinches (12.63%), and 3 potential noise levels (3.2%). Furthermore, the causal factors are searched with the fishbone diagram of the most potential hazard cases, namely chemical exposure, there are 12 factors. Followed by finding the dominant causative factors with the Nominal Group Technique (NGT) there are 7 factors. Then plan improvement of the 7 factors with the 5W + 1H method so that the level of risk of work accidents decreases.